KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA MAL PELAYANAN PUBLIK KABUPATEN PONOROGO PROPINSI JAWA TIMUR TAHUN 2022 - Cuk Hartono; Aris Tri Haryanto; Adi Purwanto (JI@P, 2023)
This research aims to describe the quality of population administration services atthe Ponorogo Regency Public Service Mall. In this study, the researchmethodology used by the author is a descriptive research method with aqualitative approach with a view to focusing attention on the problems orphenomena that existed at the time the research was conducted. The keyinformants of the research were the Head of the Department of Population andCivil Registration. To measure service quality, it is necessary to have fiveindicators or better known as 'dimensions', which include: Tangibles, reliability,responsiveness, Assurance, , Empathy.Based on the results of data presentation and analysis, it can be concluded that ingeneral the quality of population administration services at the PonorogogoRegency Public Service Mall is good, needs to be improved such as discipline inservice hours and friendliness of officers at the service counter.Keywords: Tangibles, reliability, responsiveness, assurance, empathy